Monday
March 27, 2017

Post a New Question

Posted by on .

solve.

6t + 7/ 4t - 1 = 3t +8/2t - 4

  • math - ,

    The way you typed it ....
    6t + 7/4t - 1 = 3t +8/2t - 4
    6t + (7/4)t - 1 = 3t + 4t - 4
    6t - 3t - (7/4)t = -4 + 1
    (5/4)t = -3
    t = -12/5

    I have a feeling that is not what you meant.
    Please put in the necessary brackets

    (I have a feeling you meant:
    (6t + 7)/(4t - 1) = (3t +8)/(2t - 4) )

  • math - ,

    ah your right =)

  • math - ,

    then cross-multiply
    I can see the 12t^2 on each side canceling, giving you an equation in t

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question